FACTORS CONDITIONING THE DEVELOPMENT OF SAFE FOOD PRODUCTION IN POLAND - Olga Stefko; Izabela Lipińska; Dorota Piasecka-Kwiatkowska (Journal of Agribusiness and Rural Development, 2013)
Food allergies are a serious problem of modern society. That have contributed to the creation of a separate sector that is involved in the production of foods targeted specifically for it. The aim of the article is an attempt at distinguishing the key success factors that determine not only the success but also the development of safe food production in Poland. To effect the main purpose of the paper, primary as well as secondary materials were used. The basis for the evaluation, apart from papers, making up the literature of the subject, were the results of the research conducted amongst a group of experts among whom the questionnaire was conducted. It related to multi-plane and multi-aspect conditions for the development of safe food in Poland. Then, the STEEPVL analysis and Key Success Factors method were conducted. Analyses show, that the producers of safe food which is targeted at allergic people, to develop their own businesses do not need the organizational and technological support, but mainly financial. Finding the competitive advantages is primarily at the level of skill to raise funds for small and medium-sized enterprises from the pool of national aid and the EU.